The Effect of the Pre-emtive Military Strike Doctrine on Efforts to Establish New International Legal Provisions - Peilouw, Johanis Steny Franco (SASI, 2022)
Introduction: One of the interventional measures that can be justified under international law is self-defence. When there has been an armed attack, on the condition that it is instant, overwhelming situation, leaving no means, no moment of deliberation, that is a justifiable proposition for self-defence.Purposes of the Research: To examine and analyze the influence of the doctrine of pre-emtive military strike on efforts to establish new international legal provisions.Methods of the Research: This research uses normative juridical research methods with legal materials used, namely primary legal materials, secondary legal materials and tertiary legal materials. The collection technique is carried out through literature studies and then analyzed using qualitative methods.Results of the Research: The practice of some countries today in order to anticipate such an attack, pre-emtive military strikes are carried out in the context of anticipatory self-defense, with the aim of conducting self-defense before an attack occurs. The practice of anticipatory self-defence has become a serious conversation among academics, even when the act is practiced repeatedly continuously by a number of countries and recognized for its existence, it is certain to set a precedent that leads to the creation of an international customary law. Self-defence anticipatory measures applied in the doctrine of preemptive military strike have been adopted by several countries before and after the formation of the UN organization. But this has not set a legal precedent, despite efforts to make it an International custom through the practice of countries. If this is allowed to take place, it will at some point become customary international law. The application of the preemptive military strike will affect the establishment of new international law provisions.